(untitled) (Experimental biology, 2015)
Was carried out research of antimicrobial properties of Salvia officinalis, Calendula officinalis L., Herba bidentis, Achillea millefolilius and their functionalizathion with carbonized rice husk referring to intestinal pathogens, food toxic infections and purulent inflammation bacteria – Echerichia coli, Enterococcus sp., Staphylococcus aureus, Salmonella typhimurium. Phytoextracts functionalizathion with carbonized rice husk relatively with phytoextracts showed high antimicrobial activity referring to the test cultures.